ANALISIS PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - -, MARKUS DEINDRIK (EKONOMIA, 2017)
This study aims to, know the difference in the financial performance of the acquirer companies in companies listed on the Indonesia Stock Exchange (BEI). The sample of research is four companies listed in Bursa Efek Indonesia (BEI) which active in food and beverage sector.The theory used in this research is financial ratios that use current ratio (CR), return on equity (ROE), return on asset (ROA), earnings per share (EPS), net profit margin (NPM). The study period was four years before the acquisition and four years after the acquisition. This research uses quantitative approach which is done through paired sample t-test (two paired sample t test)The results of this study indicate that there are significant differences between the financial performance before and after the acquisition based on the ratio of return on equity (ROE), return on assets (ROA), net profit margin (NPM). Current ratio (CR), earnings per share (EPS) show insignificant results.